Burden of type 2 diabetes among pulmonary and extra pulmonary tuberculosis patients diagnosed in a tertiary care institute in Puducherry - R., Sengadhir Vendhan; A., Velavan; D., Elanchezhian; M., Vasanthakogilam; Binoth, Navilson; Konduru, Rajesh Kumar (International Journal Of Community Medicine And Public Health, 2023)
Background: Most often diabetes and tuberculosis present together and complicate each other at many levels. Studies show people with diabetes were at three times higher risk of developing tuberculosis. Study done in Kerala have reported that the prevalence of diabetes is higher among males and among smear positive pulmonary tuberculosis cases. Objective was to measure the burden of type 2 diabetes mellitus among pulmonary and extra pulmonary tuberculosis patients diagnosed in a tertiary care institute in Puducherry. Methods: Data was obtained from National tuberculosis elimination programme (NTEP) referral register of Pondicherry Institute of Medical Science. All the patients who have diagnosed to have tuberculosis from January 2022 to July 2022 were included. Diabetic status among pulmonary and extrapulmonary tuberculosis patients was also collected. Results: Among the patients with tuberculosis, 67% of patients were males. A total of 38.8% of cases were found to have diabetes and out of these cases, 23.8% of patients were known case of diabetes and 16.4%of cases were patients with newly diagnosed diabetes. It is observed that, among patients with pulmonary tuberculosis, 32.8% of cases and among patients with extrapulmonary tuberculosis 5.9% of cases were found to have diabetes. Conclusions: The present study showed that burden of type 2 diabetes mellitus was more among pulmonary tuberculosis.